Giants in the landscape : monumentality and territories in the European Neolithic : proceedings of the XVII UISPP World Congress (1-7 September, Burgos, Spain). - Ard, Vincent,; Pillot, Lucile, (Archaeopress archaeology., 2016)
Proceedings from the session held at the XVII World UISPP Congress, Burgos, 2014. The session considered the various manifestations of the relationship between Neolithic enclosures and tombs in different contexts of Europe, notably through spatial analysis.